DAMPAK PROGRAM SEKOLAH PEMBERDAYAAN RAKYAT (SPR) TERHADAP PERKEMBANGAN USAHA PEMBUDIDAYA IKAN LELE DI KECAMATAN PARE - Meynanda Rosalini; Erlin Widya Fatmawati; Heru Setiyadi (LPPM UNIKS, 2026)
This research aims to describe the implementation of the People's Empowerment School (SPR) program in Pare District and analyze its impact on human resource (HR) capacity building and the business development of catfish farmers. Using a descriptive qualitative approach, the study was conducted from June to November 2025. The results indicate that the SPR program successfully transformed the farmers' paradigm from a traditional system toward structured industrial management through intensive education on technical cultivation, independent financial management, and digital marketing strategies. Increased HR capacity is evident in the respondents' ability to perform feed cost efficiency and organized business bookkeeping. Positive influences on business development include improved production quality, harvest stability, and expanded market reach via social media promotion to reduce dependency on local middlemen. Furthermore, the program strengthened solidarity and cooperation within farmer groups to enhance their market bargaining position. Overall, the SPR program provides a solid foundation for the sustainability of a professional fishery business in Pare District. Keywords: People's Empowerment School (SPR), catfish farmers, HR capacity, business development, Pare District.